2021
DOI: 10.1111/agec.12611
|View full text |Cite
|
Sign up to set email alerts
|

The impact of index‐insured loans on credit market participation and risk‐taking

Abstract: Index‐insured loans offer considerable advantages over standalone insurance policies for improving farmers’ access to agricultural credit. However, research on demand for such products and their impact on profitable investment decisions has been limited and conflicting. In this article, we investigate the impact of index insurance on demand for credit and investment decisions using a lab‐in‐the‐field experiment conducted in rural Tanzania. We find that index insurance increases demand for credit and high‐risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
1
5
0
Order By: Relevance
“…Our result that fertilizer adoption increases when farmers have access to loans bundled with micro-insurance complements numerous empirical field studies that have found a positive impact of stand-alone index insurance on technology adoption decisions (Cai et al, 2015;Elabed & Carter, 2015;Jensen & Barrett, 2017;Karlan et al, 2014;Miranda & Farrin, 2012). Our results are also consistent with theoretical research that predicts that index insurance would be effective at promoting smallholder adoption of advanced technologies when bundled with agricultural production loans (Carter et al, 2016;Dougherty et al, 2021;Farrin & Miranda, 2015;Gallenstein et al, 2021;Miranda & Gonzalez-Vega, 2011). However, our results are sparse with respect to the wide range of inputs we explore.…”
Section: Introductionsupporting
confidence: 89%
“…Our result that fertilizer adoption increases when farmers have access to loans bundled with micro-insurance complements numerous empirical field studies that have found a positive impact of stand-alone index insurance on technology adoption decisions (Cai et al, 2015;Elabed & Carter, 2015;Jensen & Barrett, 2017;Karlan et al, 2014;Miranda & Farrin, 2012). Our results are also consistent with theoretical research that predicts that index insurance would be effective at promoting smallholder adoption of advanced technologies when bundled with agricultural production loans (Carter et al, 2016;Dougherty et al, 2021;Farrin & Miranda, 2015;Gallenstein et al, 2021;Miranda & Gonzalez-Vega, 2011). However, our results are sparse with respect to the wide range of inputs we explore.…”
Section: Introductionsupporting
confidence: 89%
“…Evidence on the interest in insured loans which let the lender take a first claim on the indemnities has been mixed so far. By means of simulation (Farrin & Miranda, 2015) and experimental evidence (Galarza & Carter, 2011; Gallenstein et al., 2020) different studies confirmed that coupling loans and insurance would increase the demand for credit as there is no risk of losing the collateral. Mishra et al.…”
Section: Experimental Design and Implementationmentioning
confidence: 97%
“…Based on kinship support, the informal risk-taking network can improve the ability of farmers to resist external shocks by increasing their current income, promoting private lending, and expanding employment opportunities [23,71]. Families with weak economic vulnerability and more considerable informal risk-taking network resources are more likely to choose income diversification to maintain the smooth consumption level of families [72,73] and reduce the incidence of poverty. According to Mobarak and Rosenzweig [74], informal risk-taking networks can indirectly reduce economic vulnerability by improving the ability to access information, funds, emotional support and enhance the ability of families to resist adverse shocks.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%